2022
DOI: 10.7759/cureus.29269
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab-Induced Hypertension as a Potential Physiological Clinical Biomarker for Improved Outcomes in Patients With Recurrent Glioblastoma Multiforme: A Systematic Review

Abstract: With the advancement in medicine leading to the discovery of anti-vascular endothelial growth factor drugs, numerous oncologists are now commonly using antiangiogenic medications to improve outcomes and attain disease control. Thus, the significance of prognostic and predictive indicators in patient selection has become increasingly imperative. These biomarkers have the capacity to be highly effective and can easily be implemented in various diagnostic and therapeutic settings on a large scale. Overall, it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The most reported adverse event following administration of bevacizumab is hypertension (grade 2–3), which affects ≈40% of treated patients 24–27,38,39 (Figure 1B). Interestingly, with the exception of 1 small prospective study, 38 patients who developed hypertension following bevacizumab treatment demonstrated prolonged progression-free survival and OS, with statistically significant increases in OS ranging from 5 to 9 months compared with normotensive patients.…”
Section: Hypertension As a Biomarker Of Response To Bevacizumab Treat...mentioning
confidence: 99%
See 2 more Smart Citations
“…The most reported adverse event following administration of bevacizumab is hypertension (grade 2–3), which affects ≈40% of treated patients 24–27,38,39 (Figure 1B). Interestingly, with the exception of 1 small prospective study, 38 patients who developed hypertension following bevacizumab treatment demonstrated prolonged progression-free survival and OS, with statistically significant increases in OS ranging from 5 to 9 months compared with normotensive patients.…”
Section: Hypertension As a Biomarker Of Response To Bevacizumab Treat...mentioning
confidence: 99%
“…36 This is because bevacizumab stabilizes the vasculature by inhibiting VEGFA-induced vessel permeabilization, 37 and thereby restores blood-brain barrier integrity, leading to skewed magnetic resonance imaging readouts due to marked decreases of hyperperfusion, edema, and contrast enhancement. 36 The most reported adverse event following administration of bevacizumab is hypertension (grade 2-3), which affects ≈40% of treated patients [24][25][26][27]38,39 (Figure 1B). Interestingly, with the exception of 1 small prospective study, 38 patients who developed hypertension following bevacizumab treatment demonstrated prolonged progression-free survival and OS, with statistically significant increases in OS ranging from 5 to 9 months compared with normotensive patients.…”
Section: Hypertension As a Biomarker Of Response To Bevacizumab Treat...mentioning
confidence: 99%
See 1 more Smart Citation